Taṭbīqu Ta‘līmi al-Insyā’ fī al-Madrasah al-‘Āliyah al-Islāmiyyah al-Namūdhajiyyah Ḥafṣūtī Zain al-Ḥasan Genggong, Probolinggo: - Dewi Hikmatul Laili; Edi Kurniawan Farid; Shobirin (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2026)
Here is a refined and more academic version of your abstract, with improved fluency, coherence, and scholarly tone while keeping your meaning unchanged: This study aims to analyze the implementation of Insha’ (Arabic composition) instruction at Model Islamic Senior High School Hafsawati Zainul Hasan Genggong Probolinggo and to identify the supporting and inhibiting factors that influence students’ Arabic writing development. This research employed a qualitative descriptive approach using a case study design. The participants consisted of one Arabic language teacher and 24 eleventh-grade students selected through purposive sampling, as they were directly involved in Insha’ learning activities. Data were collected through classroom observations, semi-structured interviews, and documentation of students’ writing assignments. To ensure the validity of the data, source triangulation and methodological triangulation were applied. Data analysis followed the stages of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of Insha’ instruction was conducted through four interconnected stages: topic introduction, vocabulary and idea development, guided writing practice, and teacher evaluation. The results reveal that teacher guidance and continuous writing practice play a significant role in improving students’ ability to organize ideas and construct grammatically correct Arabic sentences. Students with a stronger vocabulary repertoire demonstrated greater confidence, accuracy, and independence in writing. In contrast, students with limited vocabulary knowledge tended to rely heavily on literal translation from Indonesian into Arabic, which negatively affected the naturalness and accuracy of their written expression. Furthermore, insufficient writing practice was found to hinder students’ ability to produce coherent and well-structured texts. This study concludes that effective Insha’ instruction requires the integration of systematic vocabulary enrichment, structured and process-oriented writing activities, and consistent practice supported by constructive feedback. Accordingly, Arabic language teachers are recommended to implement intensive vocabulary development strategies, encourage process-based writing instruction, and provide continuous corrective feedback in order to enhance students’ Arabic writing proficiency. Keywords: Insha’ instruction, Arabic writing proficiency, writing development, qualitative case study.